2018
DOI: 10.1590/1806-9282.64.07.649
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of harmonic scalpel in patients submitted to total thyroidectomy: systematic review with meta-analysis

Abstract: OBJECTIVE: The objective of this study was to evaluate the efficacy and safety of the harmonic scalpel compared to the conventional technique in patients submitted to total thyroidectomy. METHOD: This is a systematic review with inclusion of randomized controlled trials (RCTs) that compared both techniques. An electronic search was carried out in the Medline and Lilacs databases until June 2017. The outcomes analysed were operation time, intraoperative bleeding, surgical morbidity, and costs. RESULTS: Data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Harmonic devices were associated with reductions in operating time across all nine systematic reviews ranging from -0.10 min to -29.29 min compared to conventional methods [ 15 , 17 , 20 , 23 , 24 , 27 , 35 , 37 , 38 ]. A statistically significant reduction in operating time was reported for cholecystectomy [ 27 ], flap harvesting [ 24 ], gastrectomy [ 20 ], hemorrhoidectomy [ 17 ], neck dissection [ 38 ], and thyroidectomy [ 35 ]. Both systematic reviews showed lower operating time with Harmonic than ABP device comparators, but differences were not significant (Table 2 ) [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Harmonic devices were associated with reductions in operating time across all nine systematic reviews ranging from -0.10 min to -29.29 min compared to conventional methods [ 15 , 17 , 20 , 23 , 24 , 27 , 35 , 37 , 38 ]. A statistically significant reduction in operating time was reported for cholecystectomy [ 27 ], flap harvesting [ 24 ], gastrectomy [ 20 ], hemorrhoidectomy [ 17 ], neck dissection [ 38 ], and thyroidectomy [ 35 ]. Both systematic reviews showed lower operating time with Harmonic than ABP device comparators, but differences were not significant (Table 2 ) [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…3 B, Supplementary Table 7 ). Harmonic devices were associated with a reduction in LOS in all seven systematic reviews ranging from -0.01 days to -1.35 days [ 15 17 , 20 , 23 , 27 , 38 ], with results being statistically significant for cholecystectomy [ 27 ], mastectomy [ 23 ], and thyroidectomy [ 35 ]. Both systematic reviews for colectomy and thyroidectomy that compared Harmonic to ABP devices showed no significant differences for LOS (Table 2 ) [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hematomas that form in enclosed spaces can expose the pedicle to constant pressure, resulting in flap morbidities. It has been accepted that harmonic scalpels effectively enable hemostasis, resulting in less intraoperative bleeding and postoperative hematoma formation (Aires et al, 2018;Fritz et al, 2016;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The literature also has demonstrated a trend toward lowered rates of RLN injury 9 . A meta-analysis reported significant advantages in operative time and intraoperative blood loss, but not postoperative hematomas 15 . LigaSure system use was associated with shorter operative times 16–19 and hospital stays 17 .…”
mentioning
confidence: 99%
“…Several studies have evaluated the advantages and disadvantages of these devices compared with conventional techniques in thyroid surgeries 3,5–21 . Use of harmonic technology has been shown to be associated with numerous advantages over conventional hemostatic techniques, including lower cost, 3 shorter operative times, 5–14,22 less intraoperative blood loss, 14 shorter hospital stay, 8 transient hypocalcemia, 7,9,11 and less postoperative pain 7,8,11 .…”
mentioning
confidence: 99%